Clinical-Forensic Autopsy Findings to Defeat COVID-19 Disease: A Literature Review - Sessa, Francesco; Bertozzi, Giuseppe; Cipolloni, Luigi; Baldari, Benedetta; Cantatore, Santina; D’Errico, Stefano; Di Mizio, Giulio; Asmundo, Alessio; Castorina, Sergio; Salerno, Monica; Pomara, Cristoforo (Journal of clinical medicine, 2020)
The severe acute respiratory syndrome (SARS)-CoV-2 was identified for the first time in China, in December 2019. Confirmed cases of COVID-19 have been reported around the world; indeed, this infection has been declared a pandemic. Consequently, the scientific community is working hard to gain useful information about the history of this virus, its transmission, diagnosis, clinical features, radiological findings, research and development of candidate therapeutics as well as vaccines. This review aims to analyze the diagnostic techniques used to ascertain the COVID-19 infection, critically reviewing positive points and criticism for forensic implications, obviously including autopsy. Finally, this review proposes a practical workflow to be applied in the management of corpses during this outbreak of the COVID-19 infection, which could be useful in cases of future infectious disease emergencies. Analyzing the diagnostic methods, to date, virus nucleic acid RT-PCR represents the standard method used to ascertain the COVID-19 infection in living subjects and corpses, even if this technique has several criticisms: mainly, the staff should be highly specialized, working in high-throughput settings, able to handle high workloads and aware of health risks and the importance of the results. Thus, IgG/IgM serological tests have been developed, overcoming RT-qPCR duration, costs, and management, not requiring highly trained personnel. Nevertheless, serological tests present problems; the WHO recommends the use of these new point-of-care immunodiagnostic tests only in research settings. Furthermore, nothing has yet been published regarding the possibility of applying these methods during post-mortem investigations. In light of this scenario, in this review, we suggest a flow chart for the pathologist called on to ascertain the cause of death of a subject with historical and clinical findings of COVID-19 status or without any anamnestic, diagnostic, or exposure information. Indeed, the literature data confirmed the analytical vulnerabilities of the kits used for laboratory diagnosis of COVID-19, particularly during postmortem examinations. For these reasons, autopsy remains the gold standard method to ascertain the exact cause of death (from or with COVID-19 infection, or other causes), to consequently provide real data for statistical evaluations and to take necessary measures to contain the risks of the infection. Moreover, performing autopsies could provide information on the pathogenesis of the COVID-19 infection with obvious therapeutic implications.